2011
DOI: 10.1029/2010ja015773
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and trigger-associated substorms compared: Electrodynamic parameters in the polar ionosphere

Abstract: [1] An attempt is made to study the difference, if any, between the response of the polar ionosphere to spontaneous substorms and that to trigger-associated substorms in terms of electrodynamic parameters including ionospheric current vectors, the electric potential, and the current function. The results show that, in the first approximation, the ionospheric parameters for the two types of substorms are quite similar. It is therefore conceived that spontaneous substorms are not very different from trigger-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This assessment is also consistent with the finding that triggered substorms tend to be associated with larger | AL | values (Hsu & McPherron, ). Liu et al () also reported that a larger response in the polar cap potential drops for triggered than for spontaneous substorms.…”
Section: Discussionmentioning
confidence: 93%
“…This assessment is also consistent with the finding that triggered substorms tend to be associated with larger | AL | values (Hsu & McPherron, ). Liu et al () also reported that a larger response in the polar cap potential drops for triggered than for spontaneous substorms.…”
Section: Discussionmentioning
confidence: 93%
“…It should be noted that not all the response time of some processes is equal to this propagation time, especially the processes taking place in the magnetospheric tail. For instance, there are not only the trigger‐associated substorms responding to the variation of IMF in several minutes but also the spontaneous substorms which occur without obvious IMF triggering or when IMF changed several tens of minutes later [ Liu et al ., ]. Moreover, the nightside auroral brightness responds to the southward turning of the IMF with a peak delay time of ~60 min [ Liou et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies (e.g., Rostoker et al, 1983) have shown that the disturbances in the solar wind/IMF could trigger substorm. There exists a relatively stronger loading process for the substorm that occurred during a steady solar wind/IMF condition (Liu et al, 2011). Hsu and McPherron (2004) suggested the internal instability in the magnetosphere that causes the substorm is susceptible to external perturbations in the solar wind/IMF.…”
Section: Discussionmentioning
confidence: 99%